Media advocacy on the struggle for rights of women with disabilities: a case study of Drg Romi - Hetti Waluati Triana,; Nelmawarni,; Perrodin, David D.; Reflinaldi, (Penerbit Universiti Kebangsaan Malaysia, 2024)
This study aims to illustrate the struggle for the rights of women with disabilities in West Sumatra, Indonesia. In 2019, Drg Romi, a disabled female dentist, was targeted in a campaign attempting to cancel their standing as a civil servant. Data in the form of words, phrases, and sentences concerning Drg Romi in 2019 were gleaned from three West Sumatra newspapers (Haluan, Padang Ekspres, & Singgalang), which represented the total available printed media and passed the Press Council verification in West Sumatra. The data is in the form of information regarding the news production process, which was taken from the editorial leader of each newspaper. Data were collected by using observation, documentation, and interview techniques. Data analysis was conducted using qualitative techniques referred to as the extra lingual material method. The data was analyzed by writing memos during the research, coding the data, looking for themes and categories, discussing the data, and drawing conclusions. The results show that Drg Romi is positioned as both a subject and an object in the news sources. In both positions, the media managed to favorably position Drg Romi in a manner that benefited them and advocated for their fight for rights as a disabled woman.